2012
DOI: 10.1007/s10714-012-1473-x
|View full text |Cite
|
Sign up to set email alerts
|

Scalars, vectors and tensors from metric-affine gravity

Abstract: The metric-affine gravity provides a useful framework for analyzing gravitational dynamics since it treats metric tensor and affine connection as fundamentally independent variables. In this work, we show that, a metric-affine gravity theory composed of the invariants formed from non-metricity, torsion and curvature tensors can be decomposed into a theory of scalar, vector and tensor fields. These fields are natural candidates for the ones needed by various cosmological and other phenomena. Indeed, we show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 63 publications
0
26
0
Order By: Relevance
“…Second, it couples only to fermions f ⊂ . And its couplings, originating from the spin connection through the decomposition in (11), are necessarily flavor-universal. It couples to the known (leptons and quarks in the SM) and any hypothetical (say, the dark matter particle χ) fermion in the same way, with the same strength.…”
Section: Metric-affine Gravitymentioning
confidence: 99%
“…Second, it couples only to fermions f ⊂ . And its couplings, originating from the spin connection through the decomposition in (11), are necessarily flavor-universal. It couples to the known (leptons and quarks in the SM) and any hypothetical (say, the dark matter particle χ) fermion in the same way, with the same strength.…”
Section: Metric-affine Gravitymentioning
confidence: 99%
“…• In obtaining the MOND equation of motion (25) we have neglected contributions from the spatial variation of ρ. The situation can be improved by incorporating such terms from (24).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In the first, after setting a = −∇φ g with φ g being the gravitational potential, one formulates MOND as a modification in gravitational laws (see the reviews [15][16][17]). In this case, one is necessarily led to modified Newtonian gravity [18,19] or General Relativity (GR) extended by geometrical scalar and vector fields [20][21][22][23][24][25]. Besides, there are alternative approaches based on f (R) gravity [26][27][28][29], bimetric gravity [30,31], time foliation [32,33], nonlocal metric theories [34,35], Galileons [36], and Horava-Lifshitz gravity [37].…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that a matter-antimatter asymmetry generated by the Hehl-Datta cubic term [11] in the Dirac equation modified by the presence of torsion, could be at the origin of the presence of dark matter in the universe [12]. The decomposition of a metric-affine theory in scalars, vectors and tensors contribution, in a way to match the results of TeVeS phenomenology, was analyzed in [13]. The authors of [14], instead, suggested to fit Supernovae data replacing the dark matter content expected as from the ΛCDM model with a mean spin density of baryonic matter.…”
Section: Introductionmentioning
confidence: 99%